THE INFLUENCES OF COMMUNICATION AND WORK MOTIVATION OF THE GOVERNMENT OFFICIALS ON THE QUALITY OF LAND CERTIFICATION SERVICE AT THE SERVICE AT THE AGRARIA MUNICIPALITY OF SOUTH JAKARTA - Sunarto, Sunarto (Universitas Prof. Dr. Moestopo (Beragama), 2009)
Thzs research deals with the poor quality of land certification service and poor communication and working motivation of government employees at the Land Office of South Jakarta Municipality. This research design in form of explanatory survey using line statistics analysis completed 111i1h confirmation using qualitative data through participatory observation on documents and in- depth interviews lo find out the essence of what and how good communication and working motivation of employees in handling certificate applicants are. The result of the research shows that quality of communicators was the poorest, whereas the disturbance dimension was found the best. Working motivation and accountability 1vere other dimensions found the poorest compared lo other five